Answer:
see explanation
Explanation:
Note that
x = lnx ( natural logarithm)
Using the standard derivatives
(lnx ) =
,
(
x ) =
![(1)/(xlna)](https://img.qammunity.org/2022/formulas/mathematics/high-school/tx151zwc4qei1wlqnt6vn7kjyvsh1iedt6.png)
Using the chain rule
Given y = f(g(x)) , then
= f'(g(x))) × g'(x) ← chain rule
(c)
y =
(x² - 2) then
=
×
(x² - 2)
=
× 2x
=
![(2x)/((x^2-2)ln10)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2ot8fm8o7duom42zbvgnou1s6iewa4qjpq.png)
(d)
y = ln(
)
=
×
(
)
= x × -
![x^(-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/kei1b5ccb3eptn8su7hq0lalp351vyaodp.png)
= x ×
![(-1)/(x^2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/bwih4lpkx94zgfc17hnk73tlrydqhfkbd1.png)
= -
![(1)/(x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/og9piy2i0nv7i6ttlmlo7l76laa377xu73.png)